Reformatting the Russian Monetary System in Modern Conditions - Alexander N. Dubyanskiy (Современная Европа)
The article considers the question of possible ways of transformation of the Russian monetary system in modern conditions. Currently, Russia is facing tough economic and political sanctions, which encourage it to introduce fundamental structural reforms in all areas of the economy. The situation in which our country finds itself requires an adequate response in order to preserve economic sovereignty. It is required to restructure the monetary system in such a way that the economy is focused on using mainly its own resources. Modern theories of money could be the theoretical foundation for the upcoming transformations. The study concentrates on the Modern monetary Theory (MMT) and its possible implementation in the Russian economy. The interest that has arisen in this non-orthodox theory is due to many reasons, but the main one is that the monetary institutions of the leading countries of the world can no longer implement the previous monetary policy in order to stimulate economic growth. Scientists evaluate this theory ambiguously, and many researchers believe that its main provisions are divorced from economic realities, contradictory and, therefore, not acceptable as instruments of macroeconomic policy. The author's stance is that the main provisions are applicable in the Russian economy. Mainly, the idea of the sovereignty of the national currency is understood as the possibility of issuing money without regard to global financial institutions such as the IMF and the size of gold and foreign exchange reserves. As a result, this theory requires a deeper study of the influence of monetary emission on economic processes.